International tourists revisit intention: A case of the United Arab emirates / Abdul Rahim Julaimi, Salim Abdul Talib and Mohd Zulhilmi Suhaimi - Julaimi, Abdul Rahim; Abdul Talib, Salim; Suhaimi, Mohd Zulhilmi (UiTM Press, 2016)
The connection between past travel experience and tourists revisits behavioral intentions has not been widely explored, but the existing studies suggest a close relationship between them. Tourism-related products of a country can equally be construed to have effects on the attitudes of the tourists at the end of their actual visitation and satisfaction of a tourist with his or her travel experiences contribute to loyalty to a particular destination. It has also been acknowledged that destination image affects visitors’ subjective perception, consequent behaviour and destination choice. This paper is reviewing the constructs and dimensions which associated with international tourist revisit intention using the United Arab Emirates as contextual study setting and proposed the study conceptual framework.